Bodaville, Riley County - McKeon, Kevin (Kansas State University, The Chapman Center for Rural Studies, 2015)
With the general store as the heart of town, Bodaville served as both a home and a stopping point for travelers. Sources for this study include interviews, newspapers, maps, photographs, and firsthand accounts of the town of Bodaville.
Kevin McKeon, “Bodaville, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/150.
Keywords: Bodaville; General store; Riley County; Swedish Immigrants; Lasita; Mayday Township